ADOPTION OF SD-WAN TECHNOLOGY SOLUTION ACROSS ALL BRANCHES OF BANK MEGA - Febrian, Andhika; Liawatimena, Suryadiputra (I N F O R M A T I K A, 2024)
Information technology has played a crucial role in the development of modern business, including the banking sector. Bank Mega, one of Indonesia's largest banks with 380 branches across the country, faces challenges in connecting communication networks between branches and the head office. The use of Multiprotocol Label Switching (MPLS) as a solution for the Traditional Wide Area Network (WAN) has its drawbacks, such as high costs and limited flexibility. To enhance network performance, cost-efficiency, and security, Bank Mega plans to adopt Software-Defined Wide Area Networking (SD-WAN) technology. This research aims to analyze the impact of implementing SD-WAN technology on the network performance, security, and cost-efficiency of communication links in all Bank Mega branches. The research analyzes the implementation of SD-WAN technology at Bank Mega. The research results show that implementing SD-WAN has a positive impact on network performance, with significant improvements in access speed, response time, and throughput. Network security is also strengthened through advanced security features, although ongoing evaluation is necessary. Additionally, the cost efficiency of communication links increases due to optimized utilization of available communication lines, resulting in up to a 30% annual reduction in operational costs. The recommendations provided include optimal monitoring and management of SD-WAN, integration with additional security systems, regular evaluation of performance and cost efficiency, as well as investment in skills development for Human Resources (HR). Thus, this research offers guidance for Bank Mega and similar companies to effectively leverage SD-WAN technology to enhance the performance, security, and cost efficiency of their communication networks.